Epidemiological Investigation of the 2019 Dengue Outbreak in Dhaka, Bangladesh - Sabrina Yesmin; Shahnoor Sarmin; Alamgir Mustak Ahammad; Md. Abdur Rafi; Mohammad Jahid Hasan (Journal of Tropical Medicine)
Introduction. Bangladesh experienced its largest dengue epidemic in 2019. Our objective was to investigate the epidemiological, clinical, and laboratory characteristics of the hospital-admitted dengue patients during this epidemic. Methods. This cross-sectional study was conducted among 369 adult dengue patients admitted to two tertiary care hospitals in Dhaka, Bangladesh, from June to September 2019. The disease severity was determined according to the WHO’s 2009 classification. Results. The average age of the patients was 33.3 (SD 14) years with a predominance of men. Almost 10% developed severe dengue (plasma leakage 67%, clinical bleeding 25%, and organ involvement 25%). Fever, headache, retro-orbital pain, diarrhea, and warning signs such as abdominal pain, clinical fluid accumulation, and persistent vomiting were the most common clinical presentations. Thrombocytopenia, leukopenia, elevated HCT levels, and ALT/AST were common laboratory findings. Conclusions. Severe dengue was mostly attributable to plasma leakage with warning signs, especially abdominal pain, clinical fluid accumulation, persistent vomiting, and altered hematological parameters which might assist in the early prediction of severe dengue.